If At First You Don’t Succeed, …: Charles Todd Oration 2024 - Irving, Will (Journal of Telecommunications and the Digital Economy, 2024)
This is the Charles Todd Oration 2024, delivered by Will Irving on 17 October 2024 in Sydney. It outlines, from a Telstra-internal viewpoint, the various proposed network enhancements that eventually led to Australia’s National Broadband Network. It then draws lessons for the future from this history and the current state of telecommunications in Australia. The question-and-answer session after the Oration is also summarised.